QoE Optimization Based on Quality-delay Trade-off Model for Adaptive Streaming with Multiple VBR Videos - Nguyen, Thi Kim Thoa; Pham, Hong Thinh; Pham, Ngoc Nam (Old Journal, 2018)
HTTP adaptive streaming (HAS) as a part of multi-bitrate streaming, has attracted significant attention over the past few years. Although offering many advantages such as easy deployment and effective cost, HAS faces some challenges in providing users with high video quality. In managed networks (i.e., IPTV), the purely client-driven approaches of current HAS cause competing behavior, excessive quality oscillations, which negatively affect user experience. Some recent studies have proposed network-based solutions to overcome these problems; however, they just target at constant bitrate (CBR) videos. In this paper, we propose a quality optimization solution for variable bitrate (VBR) video streaming which allows components inside the network to select an appropriate version for each HAS client. The experiments in real-time conditions show that our method can provide each HAS client with the best possible quality while meeting the constraints of overall bandwidth and delay.